The Efficacy of Nitrates for Bone Health: A Systematic Review and Meta-Analysis of Observational and Randomized Controlled Studies - Liu, Weibing; Meng, Zhuoran; Wang, Ge (Frontiers in Endocrinology, 2022)
Background Although some studies have found that nitrates were beneficial for bone health, the findings are inconsistent. To assess the efficacy of nitrates for bone health, we conducted a meta-analysis. Methods PubMed, EMBASE databases, Cochrane Library for relevant articles published before December 2021 were searched. All observational and randomized controlled studies that reporting bone mineral density (BMD), fractures with nitrates use were included. A meta-analysis was performed to calculate risk ratios (RRs) for fractures, change differences for bone mineral density. Results Four cohort studies and two case-control studies examining the association between nitrates use and fractures were identified. The nitrates use was not associated with any fracture risk (RR = 0.97; 95% CI, 0.94–1.01; I2 = 31.5%) and hip fracture (RR = 0.88; 95% CI, 0.76–1.02; I2 = 74.5%). Subgroup analyses revealed no differences in fracture risk, whereas two cohort studies revealed a reduced risk of hip fracture (RR = 0.71, 95% CI, 0.58–0.86, I2 = 0.0%). There were no statistically significant differences in BMD percent changes at lumbar spine (WMD = -0.07, 95% CI,-0.78–0.65; I2 = 0.0%), total hip (WMD = -0.42, 95% CI,-0.88–0.04; I2 = 0.0%), femoral neck (WMD = -0.38, 95% CI,-1.02–0.25; I2 = 0.0%), or total body (WMD = -0.17, 95% CI,-0.51–0.17; I2 = 0.0%) in two randomized controlled trials (RCTs) compared with a placebo. Another two RCTs compared nitrates with alendronate. Nitrates were comparable to alendronate in increasing bone mineral density at lumbar spine (WMD = 0.00, 95% CI,-0.01–0.02; I2 = 0.0%). Besides, the most common adverse effect was headache, contributing to low adherence to therapy. Conclusion Our meta-analysis showed no association between nitrates use and fractures in observational studies. The results of RCTs on the usage of nitrates and their effects on BMD were inconsistent. High-quality, long-term studies are needed to clarify the efficacy of nitrates for bone health.